The entrepreneurial mindset : strategies for continuously creating opportunity in an age of uncertainty - McGrath, Rita Gunther (Harvard Business School Press, 2000)
"Using lessons drawn from leading entrepreneurs and entrepreneurial companies, The Entrepreneurial Mindset presents a set of practices for capitalizing on uncertainty and rapid change. The book provides simple but powerful ways to stop acting by the old rules and start thinking with the discipline of habitual entrepreneurs." "The Entrepreneurial Mindset is about succeeding in an unpredictable world. It will help everyone from independent entrepreneurs to managers of large corporations develop insights that others overlook, and then act on them to build the entrepreneurial organizations demanded by the future."--BOOK JACKET.